Normal Lactate and Unenhanced CT-Scan Result in Delayed Diagnosis of Acute Mesenteric Ischemia. (26th November 2020) - Nuzzo, Alexandre; Joly, Francisca; Ronot, Maxime; Castier, Yves; Huguet, Audrey; Paugam-Burtz, Catherine; Cazals-Hatem, Dominique; Tran-Dinh, Alexy; Becq, Aymeric; Panis, Yves; Bouhnik, Yoram; Maggiori, Leon; et al.
Abstract : INTRODUCTION: To investigate the factors associated with a delayed diagnosis (DD) of acute mesenteric ischemia (AMI). METHODS: An observational cohort study from an intestinal failure center. The primary outcome was DD >24 hours. RESULTS: Between 2006 and 2015, 74 patients with AMI were included and 39 (53%) had a DD. Plasma lactate <2 mmol/L (odd ratio: 3.2; 95% confidence interval: 1.1–9.1; P = 0.03) and unenhanced computed tomography scan (odds ratio: 5.9; 95% confidence interval: 1.4–25.8; P = 0.01) were independently associated with DD. DISCUSSION: Suspicion of AMI should no longer be affected by normal plasma lactate levels and should prompt evaluation by a contrast-enhanced computed tomography-scan.